Pengaruh Promosi, Harga, Dan Distribusi Terhadap Keputusan Pembelian Pakaian Pada Matahari Departemen Store Manado (Studi Kasus Di Matahari Departemen Store Manado Town Scuare) - Nangoy, Selvie; Mandey, Silvya L; Kawet, Lotje (JURNAL ILMIAH SOCIETY, 2016)
Each consumer has varied styles, and this is one thing that is very interesting to study. From generation to generation there are differences in characteristics in accordance with the times, especially when seen from the development of fashion style and fashion in every generation. In the development of competition in the corporate world, we need a strategy that is able to affect the consumers to buy the products offered, Matahari Department Store is a company that deals in the fashion world. The main character of Matahari Department Store Manado Town Square is to promote the effective promotion at affordable prices through a solid distribution to all consumers through the media and non-users of this media.Penelitian using quantitative research methods, it is tailored to the problems and objectives to be achieved in this research